Structural peculiarities and anticancer activities of two organotin compounds. Issue 10 (19th May 2017) - Grześkiewicz, Anita M.; Owczarzak, Agata; Kucińska, Małgorzata; Murias, Marek; Kubicki, Maciej
Abstract: Two new organotin compounds, triphenyl-4, 6-diamine-pyrimidine-2-thione-tin(IV) (1 ) and triphenyl-imidazoline-2-thione-chloro-tin(IV) (2 ), have been synthesized, spectroscopically and structurally characterized, and their cytotoxic activities have been tested against certain cancer cell lines. Atoms-In-Molecules approach has been applied for the description of the coordination geometry. Both complexes are active against chemotherapy-resistant SK-LMS-1 Leiomyiosarcoma cells (IC50 of 0.1 μM), and this activity is 3–4 times larger than against normal human CCD39Lu fibroblasts. The biological activity results are compared with those determined for other active organotin compounds which have Sn-S bond, and structure-activity relationships including geometry, intermolecular interactions, Hirshfeld surface parameters, etc., are discussed. Besides the anticancer activity, 2 is also unique from structural point of view as the first structure of a triphenyltin complex with Sn coordinated by both sulfur and halide. Abstract :